Kampanye Pola Makan Sehat dan Aktivitas Fisik sebagai Implementasi Health Promoting University - Rizqi Amalia Rohmah; Riska Novatsiani Pa Padja; Iskanaria Rosales Dali; Rehemah Liki; Victorianus Dangga (Berita Kedokteran Masyarakat (BKM), 2020)
Purpose: To evaluate a healthy eating campaign and physical activity program at Faculty of Agricultural Technology UGM. Methods: The team coordinated with students, student Associations, faculty leaders, department managers, and administrators of FTP UGM to carrying out health promotion programs. Program evaluation was carried out using a mixed method. Results: Program advocacy to faculty leaders resulted in to program support. Programs that were mutually agreed upon included stair stickers, acrylic posters, social media and video for physical activity campaigns and roll banners, stickers, posters and social media for healthy eating campaigns. Quantitative evaluation results showed a significant increase in knowledge (p<0.05), but there was no difference in the awareness and motivation of students before and after the intervention (p>0.05). Descriptive analysis showed that stair stickers were the most widely seen and remembered media for health promotion by FTP students (93.3%). The results of the qualitative evaluation show differences in the perception of the effectiveness of the media. Students also suggested various recommendations to develop a more robust and sophisticated media in order to enhance its effectiveness. Related to program sustainability, the Faculty of Agricultural Technology manager is committed to supporting the implementation of the Health Promoting University. Conclusion: The campaign on healthy eating and physical activity carried out as HPU implementation in FTP, needs to develop more effective media.